Black arms to hold you up : [a history of Black resistance] - Passmore, Ben (Pantheon Books, 2025)
"From the Ignatz and Eisner Award-winning cartoonist Ben Passmore comes a whirlwind graphic history of Black life, taken by force. It's the summer of 2020, and downtown Philly is up in flames. "You're not out in the streets with everyone else?" Ronnie asks his ambivalent son, Ben, shambling in with arms full of used books: the works of Malcom X, Robert F. Williams, Assata and Sanyika Shakur, among others. "Black liberation is your fight, too." So begins Black Arms to Hold You Up, a boisterous, darkly funny, and sobering march through Black militant history by political cartoonist Ben Passmore. From Robert Charles's shootout with the police in 1900, to the Black Power movement in the 1960s, to the Los Angeles and George Floyd uprisings of the 1990s and the aughts, readers will tumble through more than a century of armed resistance against the racist state alongside Ben-and meet firsthand the mothers and fathers of the movement, whose stories were as tragic as they were heroic. What, after so many decades lost to state violence, is there left to fight for? Deeply researched, vibrantly drawn, and bracingly introspective, Black Arms to Hold You Up dares to find the answer"-- Provided by publisher.